Microwave Sintered Magnesium Nanocomposite: Hybrid (Y2O3+Ni) Na-No-Size Reinforcement and Tensile Properties. Issue 4 (July 2016) - Hassan, S. Fida; Tun, Khin Sandar; Patel, F.; Al-Aqeeli, Nasser; Gupta, M.
In the present study, results revealed that strength of the microwave sintered commercially pure magnesium was significantly enhanced till 100°C due to the incorporation of hybrid (0.7 % yttria + 0.6 % nickel) nano-particle reinforcement, which diminishes gradually with a further increase in test temperature. Presence of the hybrid reinforcement particles assisted in complete recrystallization of magnesium matrix at 150°C. The hybrid reinforcement also assisted in the deformation process of magnesium and achieved large ductility at a relatively low temperature.